Kapabilitas Pemerintah Daerah Provinsi Riau: Hambatan dan Tantangan Pengendalian Kebakaran Hutan dan Lahan - Geovani Meiwanda (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2016)
Land and forest ﬁres in Riau have occurred since 1998 until last year 2015 by a haze emergency status as a result, causing economic losses, ecological and social aspects. The urgency in this study to see why the Riau provincial government off guard so persistent, because the capabilities of the system and the process will involve considering the ﬁre that occurred not once or twice only. The purpose of this research to know the capabilities being run the Riau provincial government has been in control of who impressed off guard because repeated continuously, and whether factors constraints and deﬁence inﬂuencing the capabilities of the Riau provincial government.